PRIMARY CUTANEOUS NK/T CELL LYMPHOMA-NASAL TYPE WITH CUTANEOUS ASPERGILLOSIS. A CASE REPORT AND LITERATURE REVIEW - Geetha Krishnanand; Vidya Monappa; Anuradha C.K. Rao (Our Dermatology Online, 2013)
We report a 66-year-old male who presented with a blackish discolored ulcerated nodule over the right flank of 2 months duration. Biopsy of the lesion revealed ulcerated epidermis with fungal hyphae of Aspergillus overlying dense, angiocentric atypical lymphoid infiltrate involving the dermis, and extending into sub cutis with geographic areas of necrosis. The patient had three episodes of cutaneous recurrence over a three year period. The cutaneous lymphoid infiltrates showed similar immunohistochemical profiles: LCA+, CD3€+, CD20- and CD56-. CD30 was positive in a small percentage of cells. P53 proliferation marker was strongly positive. There was no evidence of systemic involvement by the neoplastic lymphoid and fungal infiltrates. This is one amongst the rare reports of cutaneous aspergillosis with primary cutaneous NK/T cell lymphoma nasal-type.